Method for improving open-circuit voltage of solar cell by doping silver nanowire with antimony sulfide thin film
By using silver nanowire dopants in antimony sulfide thin film solar cells, the crystallinity of antimony sulfide thin film and the contact between CdS/Sb2S3 heterojunction interfaces is controlled, and the problem of open circuit voltage loss of antimony sulfide thin film solar cells is solved, achieving significant open circuit voltage improvement and conversion efficiency improvement.
Patent Information
- Application Number
- CN202411680174.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-28
AI Technical Summary
The open circuit voltage loss of antimony sulfide thin film solar cells is large, mainly due to the insufficient crystallinity of antimony sulfide thin film and poor contact with the CdS/Sb2S3 heterojunction interface.
By adding silver nanowires during hydrothermal deposition of antimony sulfide film, the ion reaction and annealing crystallization process are regulated, the bridge bonding of silver nanowires is realized, and the crystallinity of antimony sulfide film is optimized and the interface contact between CdS/Sb2S3 heterojunction is contacted.
The open circuit voltage and conversion efficiency of solar cells are significantly improved, and the optimal open circuit voltage is increased by more than 40 mV to 805 mV, effectively improving the crystallinity of antimony sulfide film and the contact quality of heterojunction interfaces.
Smart Images

Figure CN119546031A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solar cells, and in particular relates to a method for increasing the open-circuit voltage of a solar cell by doping a silver nanowire with an antimony sulfide film. Background Art
[0002] Thin film solar cells are an important direction for the future development of solar cells. Thin film solar cells have attracted much attention due to their green environmental protection, low energy consumption, and flexibility. Antimony sulfide (Sb2S3) thin films have a suitable band gap (1.73 eV) and a large absorption coefficient (10 5 cm -1 ), and its single phase composition, non-toxicity, environmental protection, and low price make it one of the most promising thin-film solar cell absorption layer materials in the future. In order to adapt to the development of the industry, antimony sulfide solar cells must develop in the direction of higher energy conversion efficiency, faster device stability, and better repeatability. At present, the efficiency of antimony sulfide solar cells still lags behind its theoretical efficiency. The factors that restrict the improvement of the efficiency of antimony sulfide solar cells are absorption layer defects and interface problems. The types of absorption layer defects mainly include V caused by S loss during high-temperature crystallization. S and Sb S In addition, incomplete crystallization of the film will also lead to the formation of recombination centers; the interface problem is mainly the CdS / Sb2S3 heterojunction interface, and the defects at the interface will lead to the recombination of carriers. Therefore, regulating the interface passivation of the absorption layer is an effective technical path to break through the battery efficiency.
[0003] The hydrothermal method for preparing antimony sulfide thin films is a hot topic in current research. Due to its easy doping and adjustable deposition rate, the prepared thin films have uniform composition and a smooth and dense surface. As an effective means of thin film optimization, Cl - 、Se 2- The scheme of ion doping to modify the defects of the absorption layer, Cl in the hydrothermal reaction - 、Se 2- The ion doping method is used to control the absorption layer film, enhance the conductivity of the film, and passivate V S Defects. The doping scheme is mainly in the form of anion doping, which has a certain passivation effect on S vacancy defects. However, Sb-related defects and heterojunction interfaces have a great influence on the open circuit voltage of solar cells, and there is still a lack of relevant methods.
[0004] The present invention proposes a method for doping hydrothermal antimony sulfide thin film with silver nanowires. The present invention finds that the silver nanowires have good conductivity and the bridge bond effect of the nanowires can play an effect of regulating ion reaction deposition and improve the crystallinity of the thin film. It is used to prepare solar cells, develop new doping systems, optimize the thin film deposition process, improve the crystallization quality of antimony sulfide thin films, and improve the open circuit voltage and conversion efficiency of solar cells. Summary of the invention
[0005] In view of the above defects or improvement needs of the prior art, the purpose of the present invention is to provide a method for improving the open circuit voltage of solar cells by using silver nanowire-doped antimony sulfide films. Silver nanowires are added during the hydrothermal deposition of antimony sulfide films to achieve silver nanowire-regulated ion reactions, and antimony sulfide film crystallization and silver nanowire doping are achieved during the annealing crystallization process. The present invention develops a new dopant for antimony sulfide films, which can be adapted to the hydrothermal deposition process. The silver nanowires melt and diffuse during the high-temperature crystallization process, thereby improving the crystallinity of the antimony sulfide film. The bridging action of the silver nanowires enables close contact at the CdS / Sb2S3 heterojunction interface, and the open circuit voltage of the solar cell is significantly improved. This solves the problem of insufficient crystallinity of antimony sulfide films and poor contact at the heterojunction interface in the prior art, which results in a large open circuit voltage loss of solar cells.
[0006] To achieve the above object, the present invention adopts the following technical solution: A method for improving the open circuit voltage of solar cells by using silver nanowire-doped antimony sulfide films. The solar cell structure from bottom to top includes an FTO substrate, a CdS electron transport layer, a silver nanowire-doped Sb2S3 absorption layer, a Spiro-OMeTAD hole transport layer, and a metal electrode. The silver nanowire doping promotes complete crystallization inside the antimony sulfide film, close contact between the CdS / Sb2S3 heterojunction interface, passivation of interface defects, suppression of carrier recombination, and improvement of the open circuit voltage of the solar cell.
[0007] Furthermore, the absorption layer is an antimony sulfide film doped with silver nanowires. During the hydrothermal reaction, the silver nanowires regulate the ionic reaction of antimony sulfide nucleation. During the annealing and crystallization of the antimony sulfide film, the silver nanowires undergo melting and diffusion, thereby optimizing the crystallization of the film and the CdS / Sb2S3 heterojunction interface contact.
[0008] The present invention also provides a method for preparing a silver nanowire-doped antimony sulfide film and a solar cell, comprising the following steps: (1) Preparation of silver nanowire doping solution: Shake the silver nanowire dispersion to prevent nanowire aggregation and precipitation, and ensure that the dispersion is uniform. Take 100-500 μL of the silver nanowire dispersion and mix it evenly with anhydrous ethanol at a volume ratio of 1:10-1:100 to obtain a silver nanowire doping solution with a concentration of 1wt%.
[0009] (2) Preparation of precursor solution: Weigh 1.06 g potassium antimony tartrate and 3.06 g sodium thiosulfate, respectively, and add them into a beaker containing 40 mL of deionized water. Stir the drugs until they are completely dissolved to obtain clear, uniform potassium antimony tartrate solution and sodium thiosulfate solution.
[0010] (3) Preparation of silver nanowire-doped antimony sulfide precursor film: Mix potassium antimony tartrate solution and sodium thiosulfate solution, keep stirring at a speed of 400 rmb / min; after mixing for 1 min, add 1-5 mL of silver nanowire-doped solution and wait for the color of the mixed solution to change from clear to slightly yellow. Then, perform a hydrothermal deposition experiment at a temperature of 130 °C and a time of 180 min.
[0011] (4) Annealing and crystallization: The deposited antimony sulfide film is placed in a tube furnace for annealing. The hydrothermal film is annealed and crystallized using a rapid thermal treatment process to obtain a silver nanowire-doped antimony sulfide film with a thickness of 350 nm.
[0012] (5) Preparation of solar cell devices: The FTO substrate was cleaned by ultrasonic cleaning, and then ultrasonically cleaned with deionized water, anhydrous ethanol, and acetone for 20-30 min, and then blown dry with high-purity nitrogen; a CdS film was deposited on the FTO substrate by chemical water bath deposition, and the deposition conditions were controlled to obtain a thickness of 60 nm; a 20 mg / mL CdCl2 anhydrous ethanol solution was spin-coated on the surface of the CdS film and annealed and crystallized; a silver nanowire-doped antimony sulfide film was prepared by the method of steps (1)-(4), and the deposition conditions were controlled to obtain a silver nanowire-doped antimony sulfide film absorption layer with a thickness of 350 nm; a Spiro-OMeTAD layer was deposited on the absorption layer by spin coating, and the thickness of the obtained film was 70 nm; Au was deposited on the surface of the Spiro-OMeTAD hole transport layer by vacuum evaporation technology to obtain a metal electrode with a thickness of 50 nm.
[0013] Furthermore, the silver nanowires used have a diameter of 10 to 50 nm, a length of 5 to 50 um, and a uniform and stable concentration of the dispersion.
[0014] Furthermore, the solvent of the silver nanowire dispersion liquid used is isopropyl alcohol.
[0015] Furthermore, the silver nanowire doping solution used is prepared using anhydrous ethanol, and the volume ratio of the silver nanowire dispersion to the anhydrous ethanol is 1:10-1:100.
[0016] Furthermore, in step (4), the temperature range for annealing and crystallizing the silver nanowire-doped antimony sulfide precursor film is 300-400° C., and the annealing time is 200-400 s.
[0017] Furthermore, in step (5), the annealing crystallization temperature is 400° C. and the annealing time is 20-30 min.
[0018] The present invention has the following characteristics and advantages: (1) The present invention uses silver nanowire dopants. Compared with common ion dopants, silver nanowires exist in the form of nanowires instead of ions, and will not directly participate in the Sb 3+ , S 2- The combined reaction exists as nanowires inside the precursor film and diffuses and disappears after the film is annealed. After applying this dopant, a good heterojunction interface contact can be formed between the antimony sulfide absorption layer and the CdS layer, the conductivity of the antimony sulfide film is improved, and the crystallinity inside the crystal is enhanced.
[0019] (2) The film-forming process of the hydrothermal method occurs in a solution system. Silver nanowires are mixed in an isopropanol solvent. This doping method is compatible with the hydrothermal deposition film system. This doping process can ensure the uniformity and stability of the entire solution system and facilitate the regulation of the entire film-forming stage of the film.
[0020] (3) The silver nanowire doping solution of the present invention is prepared using low-cost anhydrous ethanol. The doping amount can be controlled by the dilution concentration and the amount of dropwise addition. The amount of silver nanowires in the hydrothermal process affects the uniformity and density of the deposited antimony sulfide film. Changing the doping ratio of silver nanowires can effectively regulate the Sb in the hydrothermal deposition. 3+ and S 2- Combine reactions to optimize the thin film formation process.
[0021] (4) The silver nanowire-doped antimony sulfide thin-film solar cell obtained by the present invention can effectively improve the heterojunction quality and achieve a significant increase in the corresponding solar cell open-circuit voltage. Compared with the undoped device, the best device open-circuit voltage is increased by more than 40 mV, and the best open-circuit voltage reaches 805 mV, effectively improving the conversion efficiency of the solar cell.
[0022] (5) The silver nanowire-doped antimony sulfide thin-film solar cell described in the present invention has novel doping materials, a simple and feasible manufacturing process, and is suitable for use in a solution method, and has development prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the surface SEM morphology of undoped antimony sulfide used in Example 1.
[0024] Figure 2 This is the surface SEM morphology of the silver nanowire-doped antimony sulfide film in Example 1.
[0025] Figure 3 This is a cross-sectional SEM electron microscope image of the antimony sulfide film doped with silver nanowires in Example 1.
[0026] Figure 4 XRD diagrams of antimony sulfide films doped with silver nanowires of different doping concentrations in Example 1-2.
[0027] Figure 5 A schematic diagram of the structure of a silver nanowire-doped antimony sulfide thin-film solar cell provided in Example 3-7.
[0028] Figure 6 The performance curves of antimony sulfide thin-film solar cells doped with silver nanowires at different concentrations provided in Examples 3-4.
[0029] Figure 7 The statistical distribution of open circuit voltage of antimony sulfide thin film solar cells doped with silver nanowires of different concentrations provided in Example 5.
[0030] Figure 8 This is the performance curve of the silver nanowire-doped antimony sulfide thin film solar cell of Example 6.
[0031] Fig. 9 This is the performance curve of the silver nanowire-doped antimony sulfide thin film solar cell of Example 7. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0033] Example 1 Preparation method of silver nanowire doped antimony sulfide film: (1) Preparation of silver nanowire doping solution: Shake the silver nanowire isopropanol dispersion to prevent nanowires from agglomerating and precipitating, and ensure that the dispersion is uniform. Take 100 μL of the silver nanowire dispersion and mix it with anhydrous ethanol at a volume ratio of 1:100 to obtain a silver nanowire doping solution with a concentration of 1 wt%. The diameter of the silver nanowires used is 10 to 50 nm and the length is 5 to 50 μm.
[0034] (2) Preparation of precursor solution: Weigh 1.06 g potassium antimony tartrate and 3.06 g sodium thiosulfate, respectively, and add them into a beaker containing 40 mL of deionized water. Stir the drugs until they are completely dissolved to obtain clear, uniform potassium antimony tartrate solution and sodium thiosulfate solution.
[0035] (3) Preparation of silver nanowire-doped antimony sulfide precursor film: Mix potassium antimony tartrate solution and sodium thiosulfate solution and keep stirring at a speed of 400 rmb / min. After mixing for 1 min, add 1 mL of silver nanowire-doped solution and wait for the color of the mixed solution to change from clear to slightly yellow. Then, perform a hydrothermal deposition experiment at a temperature of 130 °C and a time of 180 min.
[0036] (4) Annealing and crystallization: The deposited antimony sulfide film was annealed in a tube furnace. The hydrothermal film was annealed and crystallized using a rapid thermal treatment process. The annealing temperature was 370 °C and the annealing time was 300 s. An antimony sulfide film with a thickness of 350 nm was obtained.
[0037] like Figure 1 As shown in FIG. 1 , due to the uncontrollable ion reaction, the film formation rate during the deposition process is unstable, and a large number of holes appear in the undoped film after annealing, resulting in low film quality. Figure 2 As shown, the obtained antimony sulfide film absorption layer has excellent density, the entire film is flat and pore-free, the grains are clearly visible, the grain boundaries are obvious, there are fewer inner layer unit cells, and the crystallinity inside the film is good. Figure 3 The cross-sectional SEM shows that the interface contact of the antimony sulfide film absorption layer prepared in this embodiment is good, and no obvious interface fracture occurs. Figure 4 It can be seen from the XRD that all the peaks of the antimony sulfide thin film absorption layer prepared in this example are aligned with the standard peaks, the intensity of the highest peak is relatively large, and it has an extremely narrow half-peak width, indicating that the obtained antimony sulfide thin film has no impurities and has high crystallinity.
[0038] Example 2 Preparation method of silver nanowire doped antimony sulfide film: (1) Preparation of silver nanowire doping solution: Shake the silver nanowire dispersion to prevent nanowire aggregation and precipitation, and ensure that the dispersion is uniform. Take 100 μL of the silver nanowire dispersion and mix it with anhydrous ethanol at a volume ratio of 1:50 to obtain a silver nanowire doping solution with a concentration of 2 wt%.
[0039] (2) Preparation of precursor solution: same as in Example 1.
[0040] (3) Preparation of silver nanowire-doped antimony sulfide precursor film: the same as in Example 1.
[0041] (4) Annealing and crystallization: same as in Example 1.
[0042] like Figure 4 As shown, all peaks of the antimony sulfide thin film absorption layer prepared in this embodiment are aligned with the standard peaks, the intensity of the highest peak is relatively large, and it has an extremely narrow half-peak width, indicating that the obtained antimony sulfide thin film does not have any impurity phase and has high crystallinity.
[0043] Example 3 The specific preparation process of silver nanowire doped antimony sulfide thin film solar cells: (1) Preparation of silver nanowire doping solution: the same as in Example 1.
[0044] (2) Preparation of precursor solution: same as in Example 1.
[0045] (3) Preparation of silver nanowire-doped antimony sulfide precursor film: the same as in Example 1.
[0046] (4) Annealing and crystallization: same as in Example 1.
[0047] (5) Preparation of solar cell devices: The FTO substrate was cleaned by ultrasonic cleaning, and then ultrasonically cleaned with deionized water, anhydrous ethanol, and acetone for 20 minutes, and then dried with high-purity nitrogen. A CdS film was deposited on the FTO substrate by chemical water bath deposition, and the deposition conditions were controlled to obtain a thickness of 60 nm. A 20 mg / mL CdCl2 anhydrous ethanol solution was spin-coated on the surface of the CdS film and annealed for crystallization at a temperature of 400°C for 30 minutes. A silver nanowire-doped antimony sulfide film was prepared by the method of the above steps (1) to (4), and the deposition conditions were controlled to obtain a 350 nm thick antimony sulfide film. A Spiro-OMeTAD layer was deposited on the absorption layer by spin coating, and the thickness of the obtained film was 70 nm. Au was deposited on the surface of the Spiro-OMeTAD hole transport layer by vacuum evaporation to obtain a metal electrode with a thickness of 50 nm.
[0048] Figure 5 A schematic diagram of the structure of a silver nanowire-doped antimony sulfide thin-film solar cell provided in Example 3-7.
[0049] Figure 6 The performance curves of antimony sulfide thin-film solar cells doped with silver nanowires at different concentrations provided in Examples 3-4.
[0050] Example 4 The specific preparation process of silver nanowire doped antimony sulfide thin film solar cells: (1) Preparation of silver nanowire doping solution: the same as in Example 2.
[0051] (2) Preparation of precursor solution: same as in Example 2.
[0052] (3) Preparation of silver nanowire-doped antimony sulfide precursor film: the same as Example 2.
[0053] (4) Annealing crystallization: same as Example 2.
[0054] (5) Preparation of solar cell device: same as in Example 3.
[0055] like Figure 6As shown in the figure, the performance of solar cells with different concentrations of silver nanowires doped with antimony sulfide thin films was tested. The best energy conversion efficiency of the solar cell with silver nanowires doped with antimony sulfide thin films according to the present invention was 7.8%, the opening voltage of the antimony sulfide cell was 0.791V, and the short-circuit current density was 16.1 mA / cm 2 , filling factor 61%, epitaxial growth of the interface reduces interface defects, intrachain transmission in the body reduces recombination in the body, and silver nanowire-doped antimony sulfide film is not used as the absorption layer. Other conditions are exactly the same, and its photoelectric conversion efficiency is only 6.9%, and the open circuit voltage is only 756 mV.
[0056] Example 5 The specific preparation process of different concentrations of silver nanowires doped with antimony sulfide thin film solar cells: (1) Preparation of silver nanowire doping solution: Shake the silver nanowire isopropanol dispersion to prevent nanowire aggregation and precipitation, and ensure that the dispersion is uniform. Take 100 μL of the silver nanowire dispersion and mix it with anhydrous ethanol at a volume ratio of 1:100, 1:50, 1:25, and 1:10, respectively, to obtain silver nanowire doping solutions with concentrations of 1wt%, 2wt%, 4wt%, and 10wt%.
[0057] (2) Preparation of precursor solution: same as in Example 1.
[0058] (3) Preparation of silver nanowire-doped antimony sulfide precursor film: the same as in Example 1.
[0059] (4) Annealing crystallization: same as in Example 1.
[0060] (5) Preparation of solar cell device: same as in Example 3.
[0061] like Figure 7 As shown in the figure, the performance of solar cells with different concentrations of silver nanowire-doped antimony sulfide thin films was tested to analyze the changes in the open circuit voltage of the devices. Generally, the open circuit voltage of the silver nanowire-doped antimony sulfide thin film solar cells has been significantly improved, with the open circuit voltage of the device increased by 30-40 mV, and the highest open circuit voltage reached 805 mV. However, when the silver nanowire-doped antimony sulfide thin film was not used as the absorption layer, the highest open circuit voltage was only 765mV. The increase in open circuit voltage is attributed to the optimization of the interface by silver nanowires and the regulation of the absorption layer.
[0062] Example 6 Annealing of silver nanowire-doped antimony sulfide precursor films: (1) Preparation of silver nanowire doping solution: the same as in Example 1.
[0063] (2) Preparation of precursor solution: same as in Example 1.
[0064] (3) Preparation of silver nanowire-doped antimony sulfide precursor film: the same as in Example 1.
[0065] (4) Annealing crystallization: The deposited antimony sulfide film was annealed in a tube furnace. The hydrothermal film was annealed using a rapid thermal treatment process at a temperature of 300°C and an annealing time of 300 s. An antimony sulfide film with a thickness of 350 nm was obtained.
[0066] (5) Preparation of solar cell device: same as in Example 3.
[0067] like Figure 8 As shown, when the silver nanowire-doped antimony sulfide precursor film is annealed and crystallized at a lower temperature, the performance of the solar cell is low and the efficiency of the device is only 5.5%. The lower open circuit voltage and short circuit current are the reasons for the low performance. The antimony sulfide film is incompletely crystallized inside, and the insufficient grain growth leads to the generation of carrier shunt paths inside the film, and the defects are seriously compounded.
[0068] Example 7 Annealing of silver nanowire-doped antimony sulfide precursor films: (1) Preparation of silver nanowire doping solution: the same as in Example 1.
[0069] (2) Preparation of precursor solution: same as in Example 1.
[0070] (3) Preparation of silver nanowire-doped antimony sulfide precursor film: the same as in Example 1.
[0071] (4) Annealing crystallization: The deposited antimony sulfide film was annealed in a tube furnace. The hydrothermal film was annealed using a rapid thermal treatment process at a temperature of 400°C and an annealing time of 300 s. An antimony sulfide film with a thickness of 350 nm was obtained.
[0072] (5) Preparation of solar cell device: same as in Example 3.
[0073] like Fig. 9 As shown in the figure, when the silver nanowire-doped antimony sulfide precursor film is annealed and crystallized at a higher temperature, the performance of the solar cell does not reach the most ideal state. The efficiency of the device is only 6.5%. The low open circuit voltage and fill factor are the reasons for the low performance. The antimony sulfide film is excessively crystallized inside, cracks are generated at the heterojunction interface at high temperature, the uniformity of the film is deteriorated, and the interface and bulk phase are seriously composited.
[0074] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for increasing the open circuit voltage of solar cells by doping antimony sulfide thin films with silver nanowires, characterized in that: The solar cell structure from bottom to top is FTO substrate, CdS electron transport layer, silver nanowire-doped antimony sulfide absorption layer, Spiro-OMeTAD hole transport layer, and metal electrode; among them, silver nanowire doping promotes complete crystallization inside the antimony sulfide film, close contact between the CdS / Sb2S3 heterojunction interface, passivation of interface defects, inhibition of carrier recombination, and improvement of the open circuit voltage of the solar cell.
2. The method according to claim 1, characterized in that: The absorption layer is an antimony sulfide film doped with silver nanowires. During the hydrothermal reaction, the silver nanowires regulate the ionic reaction of antimony sulfide nucleation. During the annealing and crystallization of the antimony sulfide film, the silver nanowires melt and diffuse, optimizing the crystallization of the film and the CdS / Sb2S3 heterojunction interface contact.
3. The method for increasing the open circuit voltage of solar cells by using silver nanowire-doped antimony sulfide thin films according to any one of claims 1 to 2, characterized in that: The following steps are involved: (1) Preparation of silver nanowire doping solution: Shake the silver nanowire dispersion to prevent nanowire aggregation and precipitation, and ensure that the dispersion is uniform; take 100-500 μL of the silver nanowire dispersion and mix it with anhydrous ethanol in an appropriate proportion to obtain a silver nanowire doping solution with a concentration of 1 wt%; (2) Preparation of precursor solution: Weigh 1.06 g potassium antimony tartrate and 3.06 g sodium thiosulfate, add them into 40 mL of deionized water, respectively, and stir until completely dissolved to obtain clear and uniform potassium antimony tartrate solution and sodium thiosulfate solution; (3) Preparation of silver nanowire-doped antimony sulfide precursor film: Mix potassium antimony tartrate solution and sodium thiosulfate solution, keep stirring at a speed of 400 rmb / min; add 1-5 mL of silver nanowire doping solution after mixing for 1 min, wait for the color of the mixed solution to change from clear to slightly yellow, and then perform a hydrothermal deposition experiment at a hydrothermal deposition temperature of 130 °C and a hydrothermal deposition time of 180 min; (4) Annealing and crystallization: The deposited antimony sulfide film is placed in a tube furnace for annealing. The hydrothermal film is annealed and crystallized by a heat treatment process to obtain a silver nanowire-doped antimony sulfide film with a thickness of 350 nm. (5) Preparation of solar cell devices: The FTO substrate was cleaned by ultrasonic cleaning, and then ultrasonically cleaned with deionized water, anhydrous ethanol, and acetone for 20-30 min, and then blown dry with high-purity nitrogen; a CdS film with a thickness of 60 nm was deposited on the FTO substrate by chemical water bath deposition; a 20 mg / mL CdCl2 anhydrous ethanol solution was spin-coated on the surface of the CdS film and annealed and crystallized; a silver nanowire-doped antimony sulfide film was prepared by the method of steps (1)-(4) to obtain a silver nanowire-doped antimony sulfide film absorption layer with a thickness of 350 nm; a Spiro-OMeTAD layer was deposited on the absorption layer by spin coating, and the obtained film thickness was 70 nm; Au was deposited on the surface of the Spiro-OMeTAD hole transport layer by vacuum evaporation technology to obtain a metal electrode with a thickness of 50 nm.
4. The method for increasing the open circuit voltage of solar cells by using silver nanowire-doped antimony sulfide thin films according to claim 3, characterized in that: The silver nanowires used have a diameter of 10 to 50 nm and a length of 5 to 50 um.
5. The method for increasing the open circuit voltage of solar cells by using silver nanowire-doped antimony sulfide thin films according to claim 3, characterized in that: The solvent of the silver nanowire dispersion used was isopropyl alcohol.
6. The method for increasing the open circuit voltage of solar cells by using silver nanowire-doped antimony sulfide thin films according to claim 3, characterized in that: The silver nanowire doping solution used in step (1) is prepared using anhydrous ethanol, and the volume ratio of the silver nanowire dispersion to the anhydrous ethanol is 1:10-1:
100.
7. The method for increasing the open circuit voltage of solar cells by using silver nanowire-doped antimony sulfide thin films according to claim 3, characterized in that: The temperature range of annealing crystallization in step (4) is 300-400°C, and the annealing time is 200-400s.
8. The method for increasing the open circuit voltage of solar cells by using silver nanowire-doped antimony sulfide thin films according to claim 3, characterized in that: The annealing temperature in step (5) is 400°C and the annealing time is 20-30 minutes.
Citation Information
Cited By
Silver-doped antimony sulfide thin film for indoor photovoltaic device and preparation method of silver-doped antimony sulfide thin film
CN121815939A